2015
DOI: 10.1111/imm.12544
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of activation‐induced cytidine deaminase enhances the clearance of pneumococcal pneumonia: evidence of a subpopulation of protective anti‐pneumococcal B1a cells

Abstract: SummaryWe describe a protective early acquired immune response to pneumococcal pneumonia that is mediated by a subset of B1a cells. Mice deficient in B1 cells (xid), or activation-induced cytidine deaminase (AID À/À ), or invariant natural killer T (iNKT) cells (Ja18 À/À ), or interleukin-13 (IL-13 À/À ) had impaired early clearance of pneumococci in the lung, compared with wild-type mice. In contrast, AID À/À mice adoptively transferred with AID +/+ B1a cells, significantly cleared bacteria from the lungs as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 41 publications
(94 reference statements)
2
41
0
Order By: Relevance
“…Such mini-APC exosomes with surface CD1d may stimulate tissue iNKT cells to release allergy-promoting Th2 cytokines, like IL-4 and IL-13, after interaction with host, plant or mite glycolipids. As a result, these CD1d-dependent iNKT cells may induce allergic responses against glycolipid Ag with the release of IL-4, as we showed previously in contact hypersensitivity [107], or IL-13 reacting against polysaccharides from bacteria, as we showed in a murine model of pneumococcal pneumonia [108]; or the plant pollens [101], as a requirement for eventual effector Th1 cell participation.…”
Section: Exosome Involvement In Allergic Rhinitis and Possibly In Nonsupporting
confidence: 55%
See 3 more Smart Citations
“…Such mini-APC exosomes with surface CD1d may stimulate tissue iNKT cells to release allergy-promoting Th2 cytokines, like IL-4 and IL-13, after interaction with host, plant or mite glycolipids. As a result, these CD1d-dependent iNKT cells may induce allergic responses against glycolipid Ag with the release of IL-4, as we showed previously in contact hypersensitivity [107], or IL-13 reacting against polysaccharides from bacteria, as we showed in a murine model of pneumococcal pneumonia [108]; or the plant pollens [101], as a requirement for eventual effector Th1 cell participation.…”
Section: Exosome Involvement In Allergic Rhinitis and Possibly In Nonsupporting
confidence: 55%
“…These B1a cells are activated by hapten-self complexes induced by application of the relevant hapten on mouse skin, which completes the tolerogenic procedure [2]. The strict Ag-specificity of the participating B1a cell subpopulation is due to activation induced deaminase (AID), a nuclear mutating enzyme, that acted on the DNA of these cells prior to immunization to cause mutations in the immunoglobulin V-region genes, thus encoding the Ag-specific combining sites of Ab heavy and light chains [108,194,195]. …”
Section: A Special Small Subset Of B Cells Produces the Ag-specific Amentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Yamamoto et.al. [37], demonstrated that a subset of peritoneal cavity originating B1a cells, which secreted higher affinity antigen-specific IgM, was essential for mediating early protection against pneumococci. These prior studies suggest a possible mechanism for protection against otherwise lethal WT A. baumannii via vaccination with the Δ trxA mutant in our studies.…”
Section: Discussionmentioning
confidence: 99%